Investigation of the nature of defects on the outer surface of heat-treated seamless pipes - O. V. Rozhkova (Литьë и металлургия)
Compliance with the quenching technology ensures a high-quality product with the required properties. Violation of the modes of heating for quenching and cooling during quenching leads to the formation of defects such as soft spots and quenching cracks. The presence of soft spots in the metal is unacceptable due to structural stresses and the difference in mechanical properties between the base metal and the defective areas. To remove soft spots, repeated heat treatment is required. Quenching cracks occur due to internal stresses that exceed the resistance to destruction, due to non-simultaneous transformations and thermal expansion and compression. Products with quenching cracks are the final rejects.The article examines soft spots and thermal cracks on the outer surface of seamless pipes formed during heat treatment. The results of metallographic studies of the microstructure in the defect zone are presented, and the genetic and morphological features of defects are determined and studied. The structural heterogeneity was confirmed by Rockwell hardness measurements. Based on the data obtained, the causes of defects were determined.